PENGARUH PASAR ONLINE TERHADAP MINAT BELI KONSUMEN DAN DAMPAKNYA PADA PASAR TRADISIONAL (STUDI KASUS DI PASAR TRADISIONAL KAJEN) - Dyah Ratna Rohmania (Sahmiyya, 2023)
This study intends to explain the influence of the online market on consumer buying interest and its impact on traditional markets. This study uses a qualitative approach. The data sources for this research come from books, journals, and other literature related to the influence of online markets on consumer buying interest and their impact on traditional markets, the results of observations and interviews with several respondents at the Kajen Main Market. The results of this study conclude that with the development of an increasingly modern era, technology is developing so rapidly. Online markets are starting to appear in the midst of society as an alternative to shopping. The online market provides a variety of consumer needs that can be purchased via the internet network, so that consumers can transact in all conditions. The existence of online markets can affect traditional markets, even though traditional markets have an important role in promoting economic growth. The advantages and disadvantages of online markets and traditional markets can affect consumer buying interest. Consumers who tend not to bother prefer shopping in online markets, while consumers who are too afraid of the risks of shopping online prefer to shop in traditional markets. The existence of online markets does not have a significant impact on the Kajen Main Market. This is because the Kajen Main Market is a shopping center for the community, both regional and city communities. In addition, some perishable merchandise such as vegetables and fish consumers are more inclined to shop at traditional markets than online markets.